Garden variety : the American tomato from corporate to heirloom - Hoenig, John (Arts and traditions of the table., 2018)
John Hoenig explores the path by which, over the last two centuries, the tomato went from a rare seasonal crop to America's favorite vegetable. Garden Variety illuminates American culinary culture from 1800 to the present, challenging a simple story of mass-produced homogeneity and demonstrating the persistence of diverse food cultures throughout modern America.